The organization of Golgi in Drosophila bristles requires microtubule motor protein function and a properly organized microtubule array - Melkov, Anna (PLoS One, 2019)
In the present report, we used highly elongated Drosophila bristle cells to dissect the role of dynein heavy chain (Dhc64C) in Golgi organization. We demonstrated that whereas in the bristle "somal" region Golgi units are composed of cis-, medial, and trans-Golgi compartments (“complete Golgi”), the bristle shaft contains Golgi satellites that lack the trans-Golgi compartment (hereafter referred to as “incomplete Golgi”) and which are static and localized at the base area. However, in Dhc64C mutants, the entire bristle shaft was filled with complete Golgi units containing ectopic trans-Golgi components. To further understand Golgi bristle organization, we tested the roles of microtubule (MT) polarity and the Dhc-opposing motor, kinesin heavy chain (Khc). For our surprise, we found that in Khc and Ik2(Dominant-negative (DN)) flies in which the polarized organization of MTs is affected, the bristle shaft was filled with complete Golgi, similarly to what is seen in Dhc64C flies. Thus, we demonstrated that MTs and the motor proteins Dhc and Khc are required for bristle Golgi organization. However, the fact that both Dhc64C and Khc flies showed similar Golgi defects calls for an additional work to elucidate the molecular mechanism describing why these factors are required for bristle Golgi organization.